2017
DOI: 10.2527/jas.2016.0999
|View full text |Cite
|
Sign up to set email alerts
|

Crude glycerin decreases nonesterified fatty acid concentration in ewes during late gestation and early lactation1

Abstract: Crude glycerin is a gluconeogenic substrate in ruminants and may help to decrease the occurrence of pregnancy toxemia. The objective in this trial was to determine the effects of feeding a diet containing crude glycerin on DMI, milk yield, milk composition, and blood metabolites in periparturient ewes and lamb performance. One hundred eighteen 90 (±1.1)-d pregnant Santa Inês ewes were used. After lambing, 32 ewes (62.8 ± 1.3 kg BW) were allotted in a randomized complete block design defined by prelambing diet,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In these studies, glycerol was supplemented at a percentage of inclusion on dry matter (DM) basis ranging from 3% up to 45%. Overall the metabolic effects described include an increase in glucose and a decrease in NEFA circulating concentrations [6,11,18]. Other studies in ewes also reported an increase in insulin [19][20][21], insulin-like growth factor-1 [20], and a decrease in urea circulating concentrations [20,21] after oral administration of 280 mL glycerol and 80 mL 1,2-propylene glycol daily for 4 days.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…In these studies, glycerol was supplemented at a percentage of inclusion on dry matter (DM) basis ranging from 3% up to 45%. Overall the metabolic effects described include an increase in glucose and a decrease in NEFA circulating concentrations [6,11,18]. Other studies in ewes also reported an increase in insulin [19][20][21], insulin-like growth factor-1 [20], and a decrease in urea circulating concentrations [20,21] after oral administration of 280 mL glycerol and 80 mL 1,2-propylene glycol daily for 4 days.…”
Section: Introductionmentioning
confidence: 79%
“…To identify the formulations and doses capable to induce a positive change in ewe's metabolic status we assessed their effects against those induced Letters indicate significant differences between D 0 and D 3 (before glycerol-based formulation administration) within the same group; p < 0.05 by M100. The latter dose has been indeed already evaluated for its effects on sheep metabolism and reproductive performance [8,16,18]. Obtained results shows that the high and moderate dose groups (G100, M75 and G75) showed no differences in mean glycerol plasma concentrations compared to the M100 one (Fig.…”
Section: Phasementioning
confidence: 85%
See 2 more Smart Citations
“…As for energy by-products, crude glycerin could be recommended for up to 10%, not affecting reproductive performance before and during the breeding season ( 42 ). In addition, it has a positive effect on the energy balance in the critical phases of late gestation and early lactation ( 43 ).…”
Section: Discussionmentioning
confidence: 99%